Animal health counseling and animal husbandry management towards smart, creative and independent - Azhari; Prayoga, Surya; Hasibuan, Rizki Hamdani (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Indonesia is famous for its natural diversity of flora and fauna. Opportunities are very wide open for young people, coupled with the declining interest of young people to wrestle in agriculture. With the existence of young people who are interested in the world of agriculture, it will create a tremendous impact on Indonesian agriculture, benefit the masses with a healthier and more advanced approach to using technology. In this regard, the dedication team conducts an introduction to the introduction of the world of early age livestock and health management counseling for livestock. Where farmers and ranchers here rarely get counseling and training, so many do not know about the potential of the village that can be used for their benefit without spending a large fee. The team has designed the materials needed according to the needs of farmers and ranchers so that in the future they will easily understand and apply them in their work later. This counseling was held 3 times a meeting which lasted several hours as needed. This counseling is carried out on an ongoing basis starting from the preparation of counseling, material preparation, implementation of counseling and report writing. The extension participants were aimed at farmer groups and ranchers.